Seasonal population dynamics of the Asian citrus psyllid, Diaphorina citri Kuwayama in Sarawak - Leong, Stephen Chan Teck; Abang, Fatimah; Beattie, Andrew; Kueh, Roland Jui Heng; Wong, Sing King (Science Publications, 2011)
Problem statement: Effective control of phytophagous pests requires a thorough understanding of their seasonal population dynamics, dispersion behavior, natural enemy activity and climate. To date, although very little detail information had been published on the ecology of Diaphorina citri. The objective of this investigation was to test through field experiment the hypothesis that the major factors influencing local D. citri populations particularly their seasonal population dynamics in Sarawak are (a) flushing cycles, (b) climate and (c) the impact of the primary parasitoids namely Tamarixia radiata and Diaphorencyrtus aligarhensis. Approach: Seasonal abundance D. citri was studied weekly from March 1998 to December 2000 in the 1-ha citrus honey mandarin (Citrus aurantium L.) commercial orchard at Jemukan (1° 33'N, 110° 41'E), Kota Samarahan Division, Southwest Sarawak, in Malaysia. Results: Field studies on citrus trees showed that the D. citri population fluctuates throughout the year on citrus honey mandarin in Sarawak. Generations overlapped but adult and egg population peaks for a short period generally coincided with three annual flushing cycles, in August-September, February-March and June-July between March 1998 and December 2000. Conclusion: Psyllid population levels are positively related to the availability of new shoot flushes. Psyllid populations are adversely affected by weather conditions and parasitoids. Adult psyllid populations increased exponentially during periods of flush growth and migration and dispersal of the adults was also related to flushing cycles. Dispersal and colonization of new trees is greatest in September-October, at the onset of the rainy season.